2015
DOI: 10.1002/cam4.556
|View full text |Cite
|
Sign up to set email alerts
|

Association between epithelial‐mesenchymal transition and cancer stemness and their effect on the prognosis of lung adenocarcinoma

Abstract: The epithelial‐mesenchymal transition (EMT) and cancer stemness (CS) are reported to be pivotal phenomena involved in metastasis, recurrence, and drug‐resistance in lung cancer; however, their effects on tumor malignancy in clinical settings are not completely understood. The mutual association between these factors also remains elusive and are worthy of investigation. The purpose of this study was to elucidate the association between EMT and CS, and their effect on the prognosis of patients with lung adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Therefore, these approaches targeting CDH1 may point out new orientations and hope for cancer treatment through gene-targeted therapies. Although E-cadherin was widely investigated in various solid tumors, its expression and prognostic value in hematologic malignancies especially in AML were poorly mentioned [35][36][37]. In the current study, CDH1 was significantly downregulated in AML patients as compared with healthy donors.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, these approaches targeting CDH1 may point out new orientations and hope for cancer treatment through gene-targeted therapies. Although E-cadherin was widely investigated in various solid tumors, its expression and prognostic value in hematologic malignancies especially in AML were poorly mentioned [35][36][37]. In the current study, CDH1 was significantly downregulated in AML patients as compared with healthy donors.…”
Section: Discussionmentioning
confidence: 48%
“…Although some studies have reported the importance of CAIX in prognosis of lung cancer patients , the exact mechanism remains unclear. On the other hand, our analysis of 239 resected lung adenocarcinoma specimens at our institute did not show the association of CAIX expression with patient prognosis (data not shown) . These results may provide new insights on using CAIX as a target for treating advanced lung cancer requiring induction chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 75%
“…Our results also demonstrated that CD133 expression increased in IGROV1 ∆L1CAM cells. In lung adenocarcinoma, elevated expression CD133 is a signature marker of EMT [35]. Recent studies have highlighted a link between EMT and CSC formation, indicating that stem cell-properties emerge during progression of EMT and stemness seems to be important to regulate invasive potential [36].…”
Section: Discussionmentioning
confidence: 99%